Mechanical and physical properties of wood polypropylene composites from three Malaysian wood species / Mohd Faizal Mohd Arif - Mohd Arif, Mohd Faizal (2008)
The study focuses on the effects of wood species, particle sizes and filler loading on the mechanical and physical properties of the wood polypropylene composites. The sawdust was derived from three Malaysian hardwood species; Kelempayan (Anthocephyllus cadamba) , Rubberwood (Hevea brasilliensis) and Simpoh (Dillenia reticulata) were used as filler s in polypropylene composite at 10%, 30% and 50% by weight. The particle sizes used were 40BS-mesh (354 microns), 60BS-mesh (250 microns) and unscreened. The study was statistically designed and analyzed based on a 95% confidence level (p<0 .05). The bulk density of sawdust species had significant effect on all the mechanical and physical properties. The correlation coefficient of bulk density sawdust showed insignificance effects on tensile strength, tensile modulus and tensile elongation. The analysis of variance (ANOYA) showed that compo sites containing Kelempayan and Rubberwood sawdust were observed to have insignificant effect on tensile modulus. Simpoh sawdust showed insignificant effect on tensile strength and its modulus. The correlation coefficient analysis revealed that, the composites pre sent small differences in their properties in relation to the reinforcement particle size and do not significantly influence the mechanical and physical prop erties. With increasing filler loading; flexural strength, tensile strength, tensile elongation decr eased while flexural modulus and tensile modulus increased. With higher filler loading the water absorption of all the composites increases significantly. As a conclusion, sawdust from the three Malaysian wood species without coupling agent can be use for non-moisture resistance uses and renewable products in the near future.